EXPERIMENTAL AND THERMODYNAMIC CONSTRAINTS ON THE SULPHUR YIELD OF PERALKALINE AND METALUMINOUS SILICIC FLOOD ERUPTIONS - Scaillet B.; Macdonald R. (My University, 2006)
Many basaltic flood provinces are characterized by the existence of voluminous amounts of silicic magmas, yet the role of the silicic component in sulphur emissions associated with trap activity remains poorly known. We have performed experiments and theoretical calculations to address this issue. The melt sulphur content and fluid/melt partitioning at saturation with either sulphide or sulphate or both have been experimentally determined in three peralkaline rhyolites, which are a major component of some flood provinces. Experiments were performed at 150?MPa, 800–900°C, fO2 in the range NNO – 2 to NNO + 3 and under water-rich conditions. The sulphur content is strongly dependent on the peralkalinity of the melt, in addition to fO2, and reaches 1000?ppm at NNO + 1 in the most strongly peralkaline composition at 800°C. At all values of fO2, peralkaline melts can carry 5–20 times more sulphur than their metaluminous equivalents. Mildly peralkaline compositions show little variation in fluid/melt sulphur partitioning with changing fO2 (DS ≈270). In the most peralkaline melt, DS rises sharply at fO2 > NNO + 1 to values of >500. The partition coefficient increases steadily for Sbulk between 1 and 6?wt % but remains about constant for Sbulk between 0·5 and 1?wt %. At bulk sulphur contents lower than 4?wt %, a temperature increase from 800 to 900°C decreases DS by ?10%. These results, along with (1) thermodynamic calculations on the behaviour of sulphur during the crystallization of basalt and partial melting of the crust and (2) recent experimental constraints on sulphur solubility in metaluminous rhyolites, show that basalt fractionation can produce rhyolitic magmas having much more sulphur than rhyolites derived from crustal anatexis. In particular, hot and dry metaluminous silicic magmas produced by melting of dehydrated lower crust are virtually devoid of sulphur. In contrast, peralkaline rhyolites formed by crystal fractionation of alkali basalt can concentrate up to 90% of the original sulphur content of the parental magmas, especially when the basalt is CO2-rich. On this basis, we estimate the amounts of sulphur potentially released to the atmosphere by the silicic component of flood eruptive sequences. The peralkaline Ethiopian and Deccan rhyolites could have produced ?1017 and ?1018 g of S, respectively, which are comparable amounts to published estimates for the basaltic activity of each province. In contrast, despite similar erupted volumes, the metaluminous Parana–Etendeka silicic eruptives could have injected only 4·6 ? 1015 g of S in the atmosphere. Peralkaline flood sequences may thus have greater environmental effects than those of metaluminous affinity, in agreement with evidence available from mass extinctions and oceanic anoxic events.
Keywords: silicic flood eruptions; sulphur; experiment; Ethiopia; Deccan